In-situ self-condensing hydrogel based on hydrothermal carbonization synthesis and preparation method thereof
By dissolving cellulose in plant powder using sodium hydroxide/urea system in hydrogel preparation, the large energy consumption and environmental pollution during hydrogel preparation are solved in the prior art. Problem, efficient and green hydrogel preparation is achieved, with porous properties, high swelling rate and water retention rate.
Patent Information
- Application Number
- CN202411864617.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-12-18
AI Technical Summary
The prior art has problems of large energy consumption and large environmental pollution when preparing hydrogels.
The hydrogel is generated by dissolving cellulose in plant powder using a sodium hydroxide/urea system and then performing hydrothermal carbonization reaction and in-situ self-coagulation to generate hydrogels to reduce energy consumption and secondary pollution to the environment.
This method effectively reduces energy consumption and environmental pollution, has the advantages of efficient green and waste resource reuse, and the prepared hydrogel has porous properties, high swelling rate and water retention rate.
Smart Images

Figure CN119306885B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of ecological restoration, relates to water-retaining materials and in-situ self-condensing technology, and in particular to an in-situ self-condensing hydrogel based on hydrothermal carbonization synthesis and a preparation method thereof. Background Art
[0002] Hydrogel is a polymer material with a hydrophilic three-dimensional network structure formed by chemical or physical crosslinking, which can absorb and retain a large amount of water in water, swell but not dissolve. The common method for synthesizing hydrogels is to initiate the polymerization reaction of acrylic monomers (such as acrylic acid, methacrylic acid, etc.) with free radical initiators to form hydrogels. This usually requires considering the effects of temperature, solvent, initiator and other conditions on the reaction.
[0003] Hydrothermal carbonization technology can convert biomass into hydrothermal charcoal, which can be further utilized as a high-quality fuel or carbon material. However, its by-product, hydrothermal carbonization liquid residue (i.e., HTC waste liquid), contains a variety of organic pollutants and has a high chemical oxygen demand. Direct release of it into the environment will cause serious harm to the environment.
[0004] The existing method for preparing hydrothermal carbon usually uses aqueous solution as reaction medium, straw, starch, glucose, etc. as carbon source, and reacts in a reactor to prepare hydrothermal carbon. Zhou et al. used loofah, oak chips, corn straw as carbon source, distilled water as reaction medium to prepare hydrothermal carbon and modified it to treat cadmium-contaminated soil. A large amount of organic matter will be produced through hydrolysis, cracking, polymerization reaction, etc. during the hydrothermal carbonization process. If this part of the liquid is directly discharged, it may also cause certain pollution problems, and in real life, this part of the liquid is often discarded. Ghada Kadry et al. extracted cellulose from rice straw by alkaline and acid methods, and used the prepared cellulose solution and epichlorohydrin to synthesize a new cellulose-based hydrogel. This method uses a large amount of acid and alkali to extract cellulose, which causes certain harm to the environment, and epichlorohydrin is also toxic to the human body. Ma Yanqi et al. used nanocellulose, acrylamide, N,N'-methylenebisacrylamide, and potassium persulfate to prepare polyacrylamide composite hydrogel. During the preparation process, the method reacted in a water bath at 70°C for 4 hours, and long-term heating would consume a certain amount of energy.
[0005] In addition, the invention patent application with application number 202410090042.2 discloses a highly heat-resistant and salt-resistant bio-based hydrogel particle and its preparation method and application, which include: (1) Preparation of sludge hydrothermal carbon: add sludge and water to the hydrothermal reactor, stir and mix evenly, then close the reactor, react at a certain temperature, wait for the reactor to cool down after the reaction, open the reactor to take out the mixture, filter to obtain the solid phase, dry, ball mill, sieve, and obtain sludge hydrothermal carbon; (2) Preparation of bio-based hydrogel particles: mix acrylamide and sludge hydrothermal carbon in water, after the acrylamide is completely dissolved, add a crosslinker and an initiator in sequence, perform a polymerization reaction, and obtain a hydrogel body; when the temperature drops to room temperature, mix it with water, and shear it in a shear tank for 10 to 30 minutes to obtain bio-based hydrogel particles. It uses municipal sludge as raw material, obtains hydrothermal carbon by hydrothermal carbonization of the sludge, and uses hydrothermal carbon as a filler for polyacrylamide gel to enhance the mechanical properties and heat and salt resistance of the gel.
[0006] The invention patent application with application number 202410992458.3 also discloses a method for preparing a sludge protein-based hydrogel and its application, which first adds sodium hydroxide to deionized water, adds sludge protein and carboxymethyl cellulose after the sodium hydroxide is completely dissolved, adds hydrothermal charcoal to the system after complete dissolution, and disperses it evenly by ultrasonication. Then the system is heated to 60°C, glutaraldehyde is added dropwise, and stirred at a constant speed until the solution forms a gel to obtain a sludge protein-based hydrogel. The raw materials used in this method are all environmentally friendly, non-toxic and environmentally friendly materials with little damage to the reservoir; the viscosity of the prepared sludge protein hydrogel reaches 825200mPa·s, with a large viscosity and good plugging property, and has very important application prospects in the profile control and water plugging of low permeability reservoirs. It can be used as a profile control and water plugging agent in low permeability reservoirs.
[0007] Like the above-mentioned invention patent, the existing technology has the problems of high energy consumption and secondary pollution to the environment when preparing hydrogel. Summary of the invention
[0008] The purpose of the present invention is to solve the technical problems of high energy consumption and great environmental pollution in the preparation of hydrogels in the prior art, and to provide an in-situ self-condensing hydrogel based on hydrothermal carbonization synthesis and a preparation method thereof. The hydrogel is generated by using a sodium hydroxide / urea system to dissolve cellulose in plant powder, and then performing a hydrothermal carbonization reaction and an in-situ self-condensation method, which can effectively reduce energy consumption and secondary pollution to the environment.
[0009] In order to achieve the above-mentioned purpose, the present invention specifically adopts the following technical solutions:
[0010] An in-situ self-condensing hydrogel synthesized based on hydrothermal carbonization comprises the following components, and each component is calculated in the following parts by weight:
[0011] 0.5~2.5 parts of modified hydrothermal carbon filtrate;
[0012] 0.03-0.09 parts of N,N'-methylenebisacrylamide;
[0013] 1-3 parts of acrylamide;
[0014] 0.8~1.5 parts of ammonium persulfate;
[0015] 22.5~24.5 parts of water;
[0016] The modified hydrothermal carbon filtrate includes the following components, and each component is calculated in parts by weight as follows:
[0017] 0.8~1.5 parts of plant powder;
[0018] 0.35~0.52 parts of sodium hydroxide;
[0019] Urea 0.48~0.75 parts;
[0020] 4.68~6.34 parts of water.
[0021] Further, the following components are included, and each component is calculated by the following weight parts:
[0022] 1.6 parts of modified hydrothermal carbon filtrate;
[0023] 0.04 parts of N,N'-methylenebisacrylamide;
[0024] 2.5 parts of acrylamide;
[0025] 1 part of ammonium persulfate;
[0026] Water 22.9 parts;
[0027] The modified hydrothermal carbon filtrate includes the following components, and each component is calculated in parts by weight as follows:
[0028] 1 part of plant powder;
[0029] 0.46 parts of sodium hydroxide;
[0030] 0.54 parts of urea;
[0031] 5.61 parts of water.
[0032] Further, the following components are included, and each component is calculated by the following weight parts:
[0033] 0.8 parts of modified hydrothermal carbon filtrate;
[0034] 0.08 parts of N,N'-methylenebisacrylamide;
[0035] 1.3 parts of acrylamide;
[0036] 1.4 parts of ammonium persulfate;
[0037] Water 24.1 parts;
[0038] The modified hydrothermal carbon filtrate includes the following components, and each component is calculated in parts by weight as follows:
[0039] 1.3 parts of plant powder;
[0040] 0.38 parts of sodium hydroxide;
[0041] Urea 0.69 parts;
[0042] 4.83 parts of water.
[0043] Furthermore, the plant powder is Alternanthera philoxeroides, and the particle size of the plant powder is 80-100 meshes.
[0044] A method for preparing the above-mentioned in-situ self-coagulating hydrogel based on hydrothermal carbonization synthesis comprises the following steps:
[0045] Step a, preparing a sodium hydroxide / urea mixed solution;
[0046] Weigh sodium hydroxide and urea in proportion, and use ultrapure water to dissolve the sodium hydroxide and urea to obtain a sodium hydroxide / urea mixed solution;
[0047] Step b, preparing modified hydrothermal carbon filtrate;
[0048] Weigh plant powder according to proportion, pour the plant powder into a sodium hydroxide / urea mixed solution, mix and react, and filter to obtain a modified hydrothermal carbon filtrate;
[0049] Step c, preparing mixture 1;
[0050] The modified hydrothermal carbon filtrate is diluted with ultrapure water, and mixed evenly to obtain a mixture 1;
[0051] Step d, preparing mixture 2;
[0052] N,N'-methylenebisacrylamide, acrylamide and mixture 1 are mixed uniformly according to a certain proportion, and ammonium persulfate is added according to a certain proportion, and mixed uniformly to obtain mixture 2;
[0053] Step e, preparing an in-situ self-gelling hydrogel;
[0054] The mixture 2 is placed at room temperature to react, and then washed and dried to obtain an in-situ self-gelling hydrogel.
[0055] Furthermore, in step a, when preparing the sodium hydroxide / urea mixed solution, 8 g of sodium hydroxide and 10 g of urea are weighed, mixed with ultrapure water, and then fixed to 100 mL.
[0056] Furthermore, in step b, when preparing the modified hydrothermal carbon filtrate, the plant powder and the sodium hydroxide / urea mixed solution obtained in step a are stirred at a weight ratio of 1:7 for 3 to 5 minutes, and after mixing evenly, reacted at a temperature of 160 to 200° C. for 4 to 8 hours, and filtered through a 0.45 μm filter membrane to obtain the modified hydrothermal carbon filtrate.
[0057] Furthermore, in step c, when preparing mixture 1, 0.5-2.5 mL of the modified hydrothermal carbon filtrate obtained in step b is taken and diluted to 25 mL with ultrapure water, and mixture 1 is obtained after uniform mixing.
[0058] Furthermore, in step d, when preparing mixture 2, 0.03-0.09 g of N,N'-methylenebisacrylamide, 1-3 g of acrylamide and mixture 1 obtained in step c are mixed, and then 1 g of ammonium persulfate is added and mixed evenly to obtain mixture 2.
[0059] Furthermore, in step e, when preparing the in-situ self-gelling hydrogel, the mixture 2 obtained in step d is reacted at room temperature for 24 hours, then washed with anhydrous ethanol solution for 3 to 4 times, and finally dried at 60° C. to obtain the in-situ self-gelling hydrogel.
[0060] The beneficial effects of the present invention are as follows:
[0061] 1. In the present invention, the hydrothermal carbon filtrate is prepared by using plant (Alternanthera philoxeroides) powder, sodium hydroxide and urea, and reacted with N, N'-methylenebisacrylamide, acrylamide and ammonium persulfate at room temperature to finally obtain an in-situ self-condensing hydrogel. Based on the hydrothermal carbonization and catalytic synthesis of invasive plants, the in-situ self-condensing hydrogel is finally prepared. Its components are simple and easy to obtain, and it can effectively reduce the damage caused by invasive plants to the ecology; the preparation method uses a sodium hydroxide / urea system to dissolve the cellulose in the plant powder, and then conducts a hydrothermal carbonization reaction and in-situ self-condensation to generate a hydrogel, which can effectively reduce energy consumption and secondary pollution to the environment; while solving the problems of high energy consumption and environmental pollution in the preparation of hydrogel, this method has the advantages of high efficiency, greenness and recycling of waste resources.
[0062] 2. In the present invention, compared with ordinary self-gelling hydrogels, the in-situ self-gelling hydrogel has a certain catalytic formation effect, the formation rate of in-situ self-gelling hydrogels with different ratios is also improved to a certain extent, and the preparation efficiency of in-situ self-gelling hydrogels is greatly improved.
[0063] 3. In the present invention, the in-situ self-gelling hydrogel prepared by this method has a porous property, a high swelling rate and a water retention rate. The swelling rate can reach up to 858.67%, the 24h water retention rate can reach 68.54%, and the 48h water retention rate can reach 42.81%. BRIEF DESCRIPTION OF THE DRAWINGS
[0064] Figure 1 Comparison of morphologies generated for hydrogels with different ratios;
[0065] Figure 2 is the SEM image of the fourth group of hydrogels;
[0066] Figure 3 FT-IR images of hydrogels with different ratios;
[0067] Figure 4 XRD patterns of hydrogels with different ratios. DETAILED DESCRIPTION
[0068] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments.
[0069] Therefore, based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making any creative work shall fall within the scope of protection of the present invention.
[0070] Example 1
[0071] This embodiment provides an in-situ self-condensing hydrogel synthesized based on hydrothermal carbonization, comprising the following components, and each component is calculated in the following parts by weight:
[0072] 1.6 parts of modified hydrothermal carbon filtrate;
[0073] 0.04 parts of N,N'-methylenebisacrylamide;
[0074] 2.5 parts of acrylamide;
[0075] 1 part of ammonium persulfate;
[0076] Water 22.9 parts;
[0077] The modified hydrothermal carbon filtrate includes the following components, and each component is calculated in parts by weight as follows:
[0078] 1 part of plant powder;
[0079] 0.46 parts of sodium hydroxide;
[0080] 0.54 parts of urea;
[0081] 5.61 parts of water.
[0082] The above water is ultrapure water.
[0083] The plant powder is Alternanthera philoxeroides, and the particle size of the plant powder is 80 meshes.
[0084] The method for preparing the in-situ self-gelling hydrogel comprises the following steps:
[0085] Step a, preparing a sodium hydroxide / urea mixed solution;
[0086] Sodium hydroxide and urea were weighed in proportion, dissolved in ultrapure water, and fixed to 100 mL to obtain a sodium hydroxide / urea mixed solution.
[0087] Step b, preparing modified hydrothermal carbon filtrate;
[0088] Weigh the plant powder according to the proportion, pour the plant powder into the sodium hydroxide / urea mixed solution, mix and react, and filter to obtain the modified hydrothermal carbon filtrate. The stirring time is 3 minutes, the reaction temperature after mixing is 168°C, and the reaction time is 4.5 hours; when filtering, a 0.45μm filter membrane is used for filtering.
[0089] Step c, preparing mixture 1;
[0090] Take 1 mL of the modified hydrothermal carbon filtrate, dilute it with ultrapure water to 22 mL, and mix well to obtain a mixture 1.
[0091] Step d, preparing mixture 2;
[0092] N,N'-methylenebisacrylamide and acrylamide are added to mixture 1 in proportion and mixed evenly with mixture 1, and then ammonium persulfate is added in proportion and mixed evenly to obtain mixture 2.
[0093] Step e, preparing an in-situ self-gelling hydrogel;
[0094] The mixture 2 was reacted at room temperature of 22°C for 20 hours; then washed with anhydrous ethanol solution for 3 times; finally, dried at 60°C to obtain an in-situ self-gelling hydrogel.
[0095] The in-situ self-gelling hydrogel prepared by the method has a porous property and contains -NH2, CH, C=O, and -SO3H groups on the surface, so it has a higher swelling rate and water retention rate.
[0096] Example 2
[0097] This embodiment provides an in-situ self-condensing hydrogel synthesized based on hydrothermal carbonization, comprising the following components, and each component is calculated in the following parts by weight:
[0098] 0.8 parts of modified hydrothermal carbon filtrate;
[0099] 0.08 parts of N,N'-methylenebisacrylamide;
[0100] 1.3 parts of acrylamide;
[0101] 1.4 parts of ammonium persulfate;
[0102] Water 24.1 parts;
[0103] The modified hydrothermal carbon filtrate includes the following components, and each component is calculated in parts by weight as follows:
[0104] 1.3 parts of plant powder;
[0105] 0.38 parts of sodium hydroxide;
[0106] Urea 0.69 parts;
[0107] 4.83 parts of water.
[0108] The above water is ultrapure water.
[0109] The plant powder is Alternanthera philoxeroides, and the particle size of the plant powder is 90 meshes.
[0110] The method for preparing the in-situ self-gelling hydrogel comprises the following steps:
[0111] Step a, preparing a sodium hydroxide / urea mixed solution;
[0112] Sodium hydroxide and urea were weighed in proportion, dissolved in ultrapure water, and fixed to 100 mL to obtain a sodium hydroxide / urea mixed solution.
[0113] Step b, preparing modified hydrothermal carbon filtrate;
[0114] Weigh the plant powder in proportion, pour the plant powder into the sodium hydroxide / urea mixed solution, mix and react, and filter to obtain the modified hydrothermal carbon filtrate. The stirring time is 4 minutes, the reaction temperature after mixing is 175°C, and the reaction time is 6 hours; when filtering, a 0.45μm filter membrane is used for filtering.
[0115] Step c, preparing mixture 1;
[0116] Take 1.5 mL of the modified hydrothermal carbon filtrate, dilute it with ultrapure water to 25 mL, and mix well to obtain a mixture 1.
[0117] Step d, preparing mixture 2;
[0118] N,N'-methylenebisacrylamide and acrylamide are added to mixture 1 in proportion and mixed evenly with mixture 1, and then ammonium persulfate is added in proportion and mixed evenly to obtain mixture 2.
[0119] Step e, preparing an in-situ self-gelling hydrogel;
[0120] The mixture 2 was reacted at room temperature of 23°C for 22 hours; then washed with anhydrous ethanol solution for 3 times; finally, dried at 60°C to obtain an in-situ self-gelling hydrogel.
[0121] The in-situ self-gelling hydrogel prepared by the method has a porous property and contains -NH2, CH, C=O, and -SO3H groups on the surface, so it has a higher swelling rate and water retention rate.
[0122] Example 3
[0123] This embodiment provides an in-situ self-condensing hydrogel synthesized based on hydrothermal carbonization, comprising the following components, and each component is calculated in the following parts by weight:
[0124] 2.3 parts of modified hydrothermal carbon filtrate;
[0125] 0.06 parts of N,N'-methylenebisacrylamide;
[0126] 1.8 parts of acrylamide;
[0127] 1.1 parts of ammonium persulfate;
[0128] Water 23.4 parts;
[0129] The modified hydrothermal carbon filtrate includes the following components, and each component is calculated in parts by weight as follows:
[0130] 0.9 parts of plant powder;
[0131] 0.50 parts of sodium hydroxide;
[0132] Urea 0.72 parts;
[0133] 6.17 parts of water.
[0134] The above water is ultrapure water.
[0135] The plant powder is Alternanthera philoxeroides, and the particle size of the plant powder is 100 meshes.
[0136] The method for preparing the in-situ self-gelling hydrogel comprises the following steps:
[0137] Step a, preparing a sodium hydroxide / urea mixed solution;
[0138] Sodium hydroxide and urea were weighed in proportion, dissolved in ultrapure water, and fixed to 100 mL to obtain a sodium hydroxide / urea mixed solution.
[0139] Step b, preparing modified hydrothermal carbon filtrate;
[0140] Weigh the plant powder in proportion, pour the plant powder into the sodium hydroxide / urea mixed solution, mix and react, and filter to obtain the modified hydrothermal carbon filtrate. The stirring time is 5 minutes, the reaction temperature after mixing is 188°C, and the reaction time is 7 hours; when filtering, a 0.45μm filter membrane is used for filtering.
[0141] Step c, preparing mixture 1;
[0142] Take 0.5-2.5 mL of the modified hydrothermal carbon filtrate, dilute the modified hydrothermal carbon filtrate with ultrapure water to 27 mL, and mix well to obtain a mixture 1.
[0143] Step d, preparing mixture 2;
[0144] N,N'-methylenebisacrylamide and acrylamide are added to mixture 1 in proportion and mixed evenly with mixture 1, and then ammonium persulfate is added in proportion and mixed evenly to obtain mixture 2.
[0145] Step e, preparing an in-situ self-gelling hydrogel;
[0146] The mixture 2 was reacted at room temperature of 24°C for 27 hours; then washed with anhydrous ethanol solution for 3 to 4 times; finally, dried at 60°C to obtain an in-situ self-gelling hydrogel.
[0147] The in-situ self-gelling hydrogel prepared by the method has a porous property and contains -NH2, CH, C=O, and -SO3H groups on the surface, so it has a higher swelling rate and water retention rate.
[0148] Example 4
[0149] This embodiment provides an in-situ self-condensing hydrogel synthesized based on hydrothermal carbonization, comprising the following components, and each component is calculated in the following parts by weight:
[0150] 1.2 parts of modified hydrothermal carbon filtrate;
[0151] 0.05 parts of N,N'-methylenebisacrylamide;
[0152] 2 parts of acrylamide;
[0153] 1.2 parts of ammonium persulfate;
[0154] Water 22.8 parts;
[0155] The modified hydrothermal carbon filtrate includes the following components, and each component is calculated in parts by weight as follows:
[0156] 1.4 parts of plant powder;
[0157] 0.40 parts of sodium hydroxide;
[0158] 0.52 parts of urea;
[0159] 5.24 parts of water.
[0160] The above water is ultrapure water.
[0161] The plant powder is Alternanthera philoxeroides, and the particle size of the plant powder is 80 meshes.
[0162] The method for preparing the in-situ self-gelling hydrogel comprises the following steps:
[0163] Step a, preparing a sodium hydroxide / urea mixed solution;
[0164] Sodium hydroxide and urea were weighed in proportion, dissolved in ultrapure water, and fixed to 100 mL to obtain a sodium hydroxide / urea mixed solution.
[0165] Step b, preparing modified hydrothermal carbon filtrate;
[0166] Weigh the plant powder in proportion, pour the plant powder into the sodium hydroxide / urea mixed solution, mix and react, and filter to obtain the modified hydrothermal carbon filtrate. The stirring time is 3-5 minutes, the reaction temperature after mixing is 195°C, and the reaction time is 5.2 hours; when filtering, a 0.45μm filter membrane is used for filtering.
[0167] Step c, preparing mixture 1;
[0168] Take 0.6 mL of the modified hydrothermal carbon filtrate, dilute it with ultrapure water to 24 mL, and mix well to obtain a mixture 1.
[0169] Step d, preparing mixture 2;
[0170] N,N'-methylenebisacrylamide and acrylamide are added to mixture 1 in proportion and mixed evenly with mixture 1, and then ammonium persulfate is added in proportion and mixed evenly to obtain mixture 2.
[0171] Step e, preparing an in-situ self-gelling hydrogel;
[0172] The mixture 2 was reacted at room temperature of 21°C for 25 hours; then washed with anhydrous ethanol solution for 4 times; finally, dried at 60°C to obtain an in-situ self-gelling hydrogel.
[0173] The in-situ self-gelling hydrogel prepared by the method has a porous property and contains -NH2, CH, C=O, and -SO3H groups on the surface, so it has a higher swelling rate and water retention rate.
[0174] Test example
[0175] The collected Alternanthera philoxeroides were cut into 3 cm small segments, washed with clean water, rinsed with ultrapure water three times, dried at 100 °C for 24 h, and dried to constant weight. The dried Alternanthera philoxeroides was crushed with a grinder, passed through an 80-mesh sieve, and bagged for later use.
[0176] Weigh 8 g of sodium hydroxide and 10 g of urea, dissolve them in ultrapure water, and make up to 100 mL to prepare a sodium hydroxide / urea mixed solution.
[0177] Take 3g of Alternanthera philoxeroides powder and 21mL of sodium hydroxide / urea mixed solution, stir for 4min, put into a reactor, react at 200°C for 6h, and after cooling, filter to obtain the modified HTC filtrate.
[0178] Take 0.5 mL of modified HTC filtrate and mix it evenly with 24.5 mL of ultrapure water to obtain mixture 1; then add 0.09 g of N, N'-methylenebisacrylamide and 3 g of acrylamide, stir evenly, add 1 g of ammonium persulfate, and mix well to obtain mixture 2; finally, take out mixture 2, react at room temperature for 24 hours, wash it with anhydrous ethanol three times, put it into a 60°C oven, and dry it to constant weight to obtain an in-situ self-gelling hydrogel.
[0179] Table 1 shows the hydrogels prepared using different reagent ratios, modified hydrothermal carbon filtrate addition amounts, hydrothermal carbon sintering temperatures and time conditions (all other conditions were the same).
[0180] Table 1. Hydrogel ratios under different conditions
[0181]
[0182] Table 2 shows the production amount of different groups within 24 hours. It was found that groups 5, 6, 8, and 9 could self-gel to form hydrogel within 5 minutes, and all of them had gradually produced hydrogel within 1 hour. After 24 hours, the production amount of group 9 was the largest at 26.85 g, followed by group 6 at 25.97 g.
[0183] Table 2. Comparison of production volume in different groups
[0184]
[0185] Table 3 is a comparison of the gel fraction, swelling rate, and water retention rate of different groups. The gel fraction is above 50% except for Group 3, the swelling rate can reach up to 858.67%, the 24h water retention rate can reach up to 68.54%, and the 48h water retention rate can reach up to 42.81%.
[0186] Table 3. Comparison of gel fraction, swelling rate and water retention rate of different groups
[0187]
[0188] In this experiment, after the in-situ self-gelling hydrogel was prepared according to the conditions in Table 1, the mass of the hydrogel usually increased slowly within 24 hours, and the mass basically stabilized after 24 hours and would not continue to increase in weight. Therefore, the morphologies of the 9 hydrogels after 24 hours were compared, and the following results were obtained: Figure 1 The morphology comparison of the 9 groups of in-situ self-gelling hydrogels after 24 hours is shown. Figure 1 It can be seen that the overall texture of groups 1-3 is relatively soft, and they are in a semi-formed or unformed state, while groups 4-9 are in a good formed state and have a certain strength.
[0189] The scanning electron microscope scanning imaging analysis was performed on the fourth group of in-situ self-gelling hydrogels with the best water retention effect shown in Table 1, and the results were obtained. Figure 2 The SEM images shown. Figure 2 It can be seen that it contains many honeycomb mesh structures with pores of different sizes and wide distribution.
[0190] The X-ray diffraction imaging spectrum analysis of the 9 groups of in-situ self-gelling hydrogels shown in Table 1 yielded Figure 3 The XRD pattern shown. Figure 3 It can be seen that the characteristic peaks of hydrogel can be found, indicating that the hydrogel has been successfully synthesized.
[0191] The 9 groups of in-situ self-gelling hydrogels shown in Table 1 were analyzed by Fourier transform infrared spectroscopy. Figure 4 The FT-IR graph shown. Figure 4 It can be seen that many functional groups contained in the hydrogel can be found.
Claims
1. An in-situ self-condensing hydrogel synthesized based on hydrothermal carbonization, characterized in that: The following components are included, and each component is calculated by the following weight parts: 0.5~2.5 parts of modified hydrothermal carbon filtrate; 0.03-0.09 parts of N,N'-methylenebisacrylamide; 1-3 parts of acrylamide; 0.8~1.5 parts of ammonium persulfate; 22.5~24.5 parts of water; The modified hydrothermal carbon filtrate is prepared by the following method: Step a, preparing a sodium hydroxide / urea mixed solution; Weigh sodium hydroxide and urea in proportion, dissolve the sodium hydroxide and urea in ultrapure water, and make the volume to 100 mL to obtain a sodium hydroxide / urea mixed solution; Step b, preparing modified hydrothermal carbon filtrate; Weigh plant powder according to proportion, pour the plant powder into a sodium hydroxide / urea mixed solution, mix and react, and filter to obtain a modified hydrothermal carbon filtrate; In step a and step b, each component is calculated by the following weight parts: 0.8~1.5 parts of plant powder; 0.35~0.52 parts of sodium hydroxide; Urea 0.48~0.75 parts; Ultrapure water 4.68~6.34 parts.
2. The in-situ self-condensing hydrogel synthesized based on hydrothermal carbonization according to claim 1, characterized in that: The following components are included, and each component is calculated by the following weight parts: 1.6 parts of modified hydrothermal carbon filtrate; 0.04 parts of N,N'-methylenebisacrylamide; 2.5 parts of acrylamide; 1 part of ammonium persulfate; Water 22.9 parts; The modified hydrothermal carbon filtrate is prepared by the following method: Step a, preparing a sodium hydroxide / urea mixed solution; Weigh sodium hydroxide and urea in proportion, dissolve the sodium hydroxide and urea in ultrapure water, and make the volume to 100 mL to obtain a sodium hydroxide / urea mixed solution; Step b, preparing modified hydrothermal carbon filtrate; Weigh plant powder according to proportion, pour the plant powder into a sodium hydroxide / urea mixed solution, mix and react, and filter to obtain a modified hydrothermal carbon filtrate; In step a and step b, each component is calculated by the following weight parts: 1 part of plant powder; 0.46 parts of sodium hydroxide; 0.54 parts of urea; 5.61 parts of ultrapure water.
3. The in-situ self-condensing hydrogel synthesized based on hydrothermal carbonization according to claim 1, characterized in that: The following components are included, and each component is calculated by the following weight parts: 0.8 parts of modified hydrothermal carbon filtrate; 0.08 parts of N,N'-methylenebisacrylamide; 1.3 parts of acrylamide; 1.4 parts of ammonium persulfate; Water 24.1 parts; The modified hydrothermal carbon filtrate is prepared by the following method: Step a, preparing a sodium hydroxide / urea mixed solution; Weigh sodium hydroxide and urea in proportion, dissolve the sodium hydroxide and urea in ultrapure water, and make the volume to 100 mL to obtain a sodium hydroxide / urea mixed solution; Step b, preparing modified hydrothermal carbon filtrate; Weigh plant powder according to proportion, pour the plant powder into a sodium hydroxide / urea mixed solution, mix and react, and filter to obtain a modified hydrothermal carbon filtrate; In step a and step b, each component is calculated by the following weight parts: 1.3 parts of plant powder; 0.38 parts of sodium hydroxide; Urea 0.69 parts; 4.83 parts of ultrapure water.
4. The in-situ self-condensing hydrogel synthesized based on hydrothermal carbonization according to claim 1, characterized in that: The plant powder is Alternanthera philoxeroides, and the particle size of the plant powder is 80-100 meshes.
5. A method for preparing an in-situ self-coagulating hydrogel based on hydrothermal carbonization synthesis as claimed in any one of claims 1 to 4, characterized in that: The steps include: Step a, preparing a sodium hydroxide / urea mixed solution; Weigh sodium hydroxide and urea in proportion, and use ultrapure water to dissolve the sodium hydroxide and urea to obtain a sodium hydroxide / urea mixed solution; Step b, preparing modified hydrothermal carbon filtrate; Weigh plant powder according to proportion, pour the plant powder into a sodium hydroxide / urea mixed solution, mix and react, and filter to obtain a modified hydrothermal carbon filtrate; Step c, preparing mixture 1; The modified hydrothermal carbon filtrate is diluted with ultrapure water, and mixed evenly to obtain a mixture 1; Step d, preparing mixture 2; N,N'-methylenebisacrylamide, acrylamide and mixture 1 are mixed uniformly according to a certain proportion, and ammonium persulfate is added according to a certain proportion, and mixed uniformly to obtain mixture 2; Step e, preparing an in-situ self-gelling hydrogel; The mixture 2 is placed at room temperature to react, and then washed and dried to obtain an in-situ self-gelling hydrogel.
6. The preparation method according to claim 5, characterized in that: In step b, when preparing the modified hydrothermal carbon filtrate, the plant powder and the sodium hydroxide / urea mixed solution obtained in step a are stirred at a weight ratio of 1:7 for 3 to 5 minutes, and after mixing evenly, reacted at a temperature of 160 to 200° C. for 4 to 8 hours, and filtered through a 0.45 μm filter membrane to obtain the modified hydrothermal carbon filtrate.
7. The preparation method according to claim 5, characterized in that: In step c, when preparing mixture 1, 0.5-2.5 mL of the modified hydrothermal carbon filtrate obtained in step b is taken and diluted to 25 mL with ultrapure water, and the mixture is mixed evenly to obtain mixture 1.
8. The preparation method according to claim 5, characterized in that: In step d, when preparing mixture 2, 0.03-0.09 g of N,N'-methylenebisacrylamide, 1-3 g of acrylamide and mixture 1 obtained in step c are mixed, and then 1 g of ammonium persulfate is added and mixed evenly to obtain mixture 2.
9. The preparation method according to claim 5, characterized in that: In step e, when preparing the in-situ self-gelling hydrogel, the mixture 2 obtained in step d is reacted at room temperature for 24 hours, then washed with anhydrous ethanol solution for 3 to 4 times, and finally dried at 60° C. to obtain the in-situ self-gelling hydrogel.
Citation Information
Patent Citations
High-temperature-resistant salt-tolerant bio-based hydrogel particle as well as preparation method and application thereof
CN118126265A
Preparation method and application of sludge protein-based hydrogel
CN118755108A
Flame-retardant microcrystalline cellulose / hydroxyapatite composite aerogel and preparation method thereof
CN108238595A
Method for preparing functional group-rich gel adsorbent from straw and sludge
CN117380168A